The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.20524/aog.2018.0328
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation: donor relation, fresh or frozen, delivery methods, cost-effectiveness

Abstract: Fecal microbiota transplantation (FMT) has evolved into a robust and efficient means for treating recurrent Clostridium difficile infection (CDI). Our narrative review looks at the donor selection, preparation, delivery techniques and cost-effectiveness of FMT. We searched electronic databases, including PubMed, MEDLINE, Google Scholar, and Cochrane Databases, for studies that compared the biological effects of donor selection, fresh or frozen fecal preparation, and various delivery techniques. We also evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 97 publications
1
83
0
Order By: Relevance
“…Similarly, protocols using fresh versus frozen preparations also had no significant difference in terms of overall success rate. These results are consistent with recently published randomized control trials which reported similar findings . We recommend that institutions continue to use what is most convenient and accessible until further protocol standardization is possible.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, protocols using fresh versus frozen preparations also had no significant difference in terms of overall success rate. These results are consistent with recently published randomized control trials which reported similar findings . We recommend that institutions continue to use what is most convenient and accessible until further protocol standardization is possible.…”
Section: Discussionsupporting
confidence: 91%
“…It is not clear whether fresh or frozen-thawed microbiota improves the efficiency of FMT; however, frozen-thawed microbiota is a more convenient method (36,37). Hamilton et al (38) reported the successful use of standardized, partially purified and frozen fecal microbiota to treat C. difficile infection.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic role of FMT in UC varies in different reports, as evidenced by the rate of clinical response ranging between 39 and 55% in four RCTs investigating the use of FMT in UC (55). Ramai et al (36) reported that the clinical response in patients at 1 month and 3 months after FMT was 74.3 and 51.4%, respectively. A pilot study in India reported 87.1% clinical response, 58.1% endoscopic remission and 45.2% histological remission at week 48 post-FMT (29).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, FMT has the potential for enormous positive public health impact, preventing tens of thousands of CDI episodes every year. The FDA's policy of enforcement discretion, permitting the use of FMT to treat multiply recurrent CDI without an Investigational New Drug application, has enabled widespread use of this therapy (15). Stool banks have also played a key role in expanding safe access to FMT material that can be consistently screened in accordance with international guidelines (10).…”
Section: Discussionmentioning
confidence: 99%